Global Human Embryonic Stem Cell Laws and Policies and Their Influence on Stem Cell Tourism - Gopalan, Nishakanthi; Nor, Siti Nurani Mohd; Mohamed, Mohd Salim (Mary Ann Liebert, 2018)
Stem cell (SC) technology has spurred many debates among experts which highlight both the deficiency of current regulation and the growing need for better oversight. The benefit of better regulating SC technology is easily understood by studying the variety of laws and policies available. Previous compilations, last published in 2009, are outdated, calling for an update. Therefore, this study aims to bring up to date the laws and policies relating to human embryonic stem cells (HESC) and to identify emerging trends in regulation. The review of numerous legal documents, including bills and legislation, accessed through official government portals, found that all developed countries have sound legislation promoting research. While some developed nations have gaps within their otherwise-sound regulation, a more pressing issue is growing travel for treatment (''SC tourism'') to developing and under-developed countries where SC technology is under-or unregulated. Therefore, SC tourism is no longer a country issue; rather, it is a universal dilemma requiring international effort for a resolution.